The cry of the Halidon - Ludlum, Robert, 1927-2001. (London: Orion Books Ltd., 1975)
From the bestselling master of the high-voltage international thriller comes a must-read for every fan of vintage Ludlum. A scientist receives an offer he can't refuse--two million dollars for a geoogical survey of Jamaica's dark interior. But when British Intelligence gets wind of his mission, they let him in on a little secret--the last survey team never came back. Alex McAuliff has received an offer he can't refuse: two million dollars for a geological survey of Jamaica's dark interior. All Dunstone, Limited, requires is his time, his expertise, and his absolute secrecy. No one--not even McAuliff's handpicked team--can know of Dunstone's involvement. But British Intelligence is aware of the deal and they've let Alex in on a secret of their own: the last survey team Dunstone dispatched to Jamaica vanished without a trace. Now it's too late to turn back. Alex already knows about Dunstone...which means he knows too much. From the moment he lands in Jamaica, Alex is a marked man. But who wants him dead? Dunstone? A rival company? Or British Intelligence? Here in an island paradise where even a beautiful woman might be a spy, every move could be his last, and his only clue to survival is a single mysterious word: Halidon
Previously published in 1974 under the name Jonathan Ryder
Keywords: Geological surveys -- -- Fiction; Jamaica -- -- Fiction